Depression severity and chronic disease risk: interactive effects on cognitive function and life satisfaction in Chinese middle-aged and older adults - Li, Bowen; Guan, Siyu; Huang, Chuan; Li, Chen; Du, Yiran; Wan, Chunxiao (Frontiers in Public Health, 2025)
IntroductionMental health problems, particularly depression, are intricately linked to chronic diseases and significantly impact overall health outcomes. This study aims to investigate the dose-response relationship between depression severity and risks of heart disease, stroke, and other mental disorders, and to examine the interactive effects of depression and chronic conditions (hypertension and diabetes) on cognitive function, life satisfaction, and episodic memory among Chinese adults aged 45 and above.MethodsUsing data from the China Health and Retirement Longitudinal Study (CHARLS), 13,930 participants aged 45 and above were analyzed across five waves from 2011 to 2020. Depression was measured with the CES-D-10 scale, and participants were grouped based on symptom severity. Logistic regression models were used to examine disease risks, while linear regression models assessed the interactive effects on cognitive outcomes.ResultsLogistic regression models showed that higher levels of depression were significantly associated with increased risk of heart disease, while showing more complex relationships with stroke and mental illness risks. Subgroup analysis using linear regression indicated that coexisting conditions like hypertension and diabetes intensified the negative impact of depression on cognitive abilities, life satisfaction, and episodic memory.DiscussionThese findings underscore the necessity of integrating mental health management into rehabilitation strategies for patients with chronic illnesses. The study suggests that addressing mental health, particularly among high-risk older adult populations with chronic diseases, may improve recovery outcomes, reduce rehabilitation duration, and enhance quality of life based on the observed associations. This highlights the importance of comprehensive care that combines mental and physical health interventions to optimize rehabilitation outcomes.